PENGARUH MEDIA OVERHEAD PROJECTOR DAN PEMBERIAN LEMBAR KERJA SISWA TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DAN BAHASA INDONESIA - La Maskone (LPPM Universitas Terbuka, 2011)
Improving educational quality is a continous procceses done by teachers. One of the strategy to improve the quality is to improve substance or content delivery. This study attempt to elaborate the effect of using overhead projector (OHP) media in lecturing method for Civic and Bahasa Indonesia for high school students. Experiment approach was used to answer research questions. Factorial design was selected to reveal the research outcomes. The result showed that there was significant impact of using OHP to support learning process on Civic and Bahasa Indonesia.